An analysis on the impact that droughts have had on both the quality and quantity of Cabernet Sauvignon wine grapes in the Stellenbosch region - Freemantle, Lennox John (Stellenbosch : Stellenbosch University, 2020)
Thesis (MCom)--Stellenbosch University, 2020.